Serum diiodotyrosine – a biomarker to differentiate destructive thyroiditis from Graves' disease. Issue 2 (6th January 2022) - Fujita, Naoya; Ono, Yosuke; Sano, Azusa; Kimata, Motohiro; Oyama, Seigo; Hashimoto, Kenichi; Sato, Ikuya; Kudo, Masahiko; Miyashiro, Yoshimichi; Fujikata, Akira; Tanaka, Yuji
Abstract: Objective: Conventional diagnostic methods are limited in their ability to differentiate destructive thyroiditis from Graves' disease. We hypothesised that serum diiodotyrosine (DIT) and monoiodotyrosine (MIT) levels could be biomarkers for differentiating destructive thyroiditis from Graves' disease. Design: Patients with destructive thyroiditis ( n   = 13) and Graves' disease ( n   = 22) were enrolled in this cross-sectional study. Methods: We assayed the serum DIT and MIT levels using liquid chromatography-tandem mass spectrometry. A receiver operating characteristic (ROC) curve analysis was used to determine the sensitivity and specificity of the serum DIT and MIT levels as biomarkers for differentiating destructive thyroiditis from Graves' disease. Results: The serum DIT and MIT levels were significantly higher in patients with destructive thyroiditis than in those with Graves' disease. The ROC curve analysis showed that the serum DIT levels (≥359.9 pg/mL) differentiated destructive thyroiditis from Graves' disease, significantly, with 100.0% sensitivity and 95.5% specificity ( P < 0.001). The diagnostic accuracy of the serum MIT levels (≥119.4 pg/mL) was not as high as that of the serum DIT levels (sensitivity, 84.6%; specificity, 77.3%; P  = 0.001). Conclusions: The serum DIT levels may serve as a novel diagnostic biomarker for differentiating destructive thyroiditis from Graves' disease.